A test of collusive behavior based on incentives - Cabral, Ricardo (2018)
This paper proposes a novel collusion test based on the analysis of incentives faced by each firm in a colluding coalition. In fact, once collusion is in effect, each colluding firm faces the incentive to secretly deviate from the agreement, since it thereby increases its profits, although the colluding firms’ joint profit decreases. Thus, in a colluding coalition each firm has marginal revenues, calculated with Nash conjectures, which are larger than its marginal costs. The collusion test is based on the rejection of the null hypothesis that the firm marginal revenues with Nash conjectures are equal to or less than its marginal costs.